Synthesis, characterization, and properties of aniline-p-phenylenediamine copolymers. (May 2013) - Li, Tingxi; Yuan, Chengqian; Zhao, Yuhua; Chen, Quanliang; Wei, Meng; Wang, Yanmin
Polyaniline (PANI), poly(aniline- co - p -phenylenediamine) (P(Ani- co - p PD)), and poly( p -phenylenediamine) (P p PD) have been synthesized by oxidative polymerization using ammonium persulphate as an oxidant in hydrochloric acid medium. Several important properties such as solubility, electrical conductivity, and crystallinity of these polymers were comprehensively compared. The polymers were characterized by infrared spectroscopy, x-ray diffraction, thermogravimetry, scanning electron microscopy, and a four-point probe conductivity method. The results reveal that PANI shows the maximum conductivity and thermal stability among the polymers; P(Ani- co - p PD) exhibits the best solubility, P p PD presents the highest crystallinity, and all the polymers exist in granular morphology.